Sebaceous Carcinoma of the Vulva: An Unexpected Diagnosis and Literature Review - Rocha, Ana Carolina; Sá, Maria Inês; Abrantes, Carlos; Sousa, Rita (Acta Médica Portuguesa, 2022)
Sebaceous carcinoma of the vulva is a rare malignancy of the sebaceous glands, with potentially aggressive behaviour, that is usually found in the peri-ocular area. Nonetheless, there are sebaceous glands in the vulva and this diagnosis is especially rare, with only ten cases described in the literature. We report a case of 78-year-old female patient who presented with vulvar pruritus, previously treated with topical steroid and antifungal treatments, without improvement. The vulvar examination showed a visible yellow papule, 12 x 10 mm on the right major labia, which was biopsied and the microscopic examination revealed an invasive sebaceous carcinoma of the vulva, with an in situ component. We performed an uneventful excisional biopsy, followed by a subsequent margin widening. Three months after the diagnosis, she presented with the first recurrence. Two and half years after the diagnosis, she recurred with a larger lesion (13 mm) in the upper half of small right lip, more than 10 mm away from the midline. In a multidisciplinary meeting it was decided that the patient should undergo partial right vulvectomy with homolateral inguino-femoral sentinel node biopsy (one negative node). There was no evidence of recurrence one-year post-surgery.